Penerapan Isak 35 Dalam Penyajian Laporan Keuangan Pada Masjid Besar Jampang Kulon - Iqbal Husaeni; Evi Martaseli; Andri Indrawan (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
The objectives of this study are: To explain management of the Mosque, To explain Mosque financial reporting, To explain the application of ISAK 35 in presentation of Mosque financial report. This research uses qualitative methods with a descriptive approach, Data collection techniques using observation, interviews, and documentation, Data analysis techniques used are: data collection, data reduction, data presentation and conclusion making or verification. The results of study show: The management of the financial report of the Great Mosque of Jampang Kulon still uses the manual method which only record cash receipt and disbursement, Financial reporting at the Great Mosque of Jampang Kulon is still simple reporting cash receipts and disbursement, Presentation of financial report Mosque still have not implemented financial report ISAK 35.